Verifying the Charge‐Transfer Mechanism in S‐Scheme Heterojunctions Using Femtosecond Transient Absorption Spectroscopy - Cheng, Chang; Zhang, Jianjun; Zhu, Bicheng; Liang, Guijie; Zhang, Liuyang; Yu, Jiaguo (Angewandte Chemie International Edition, 2023)
The S‐scheme heterojunction is flourishing in photocatalysis because it concurrently realizes separated charge carriers and sufficient redox ability. Steady‐state charge transfer has been confirmed by other methods. However, an essential part, the transfer dynamics in S‐scheme heterojunctions, is still missing. To compensate, a series of cadmium sulfide/pyrene‐alt‐difluorinated benzothiadiazole heterojunctions were constructed and the photophysical processes were investigated with femtosecond transient absorption spectroscopy. Encouragingly, an interfacial charge‐transfer signal was detected in the spectra of the heterojunction, which provides solid evidence for S‐scheme charge transfer to complement the results from well‐established methods. Furthermore, the lifetime for interfacial charge transfer was calculated to be ca. 78.6 ps. Moreover, the S‐scheme heterojunction photocatalysts exhibit higher photocatalytic conversion of 1,2‐diols and H2 production rates than bare cadmium sulfide. The construction of CdS/pyrene‐alt‐difluorinated benzothiadiazole (PDB) inorganic/organic S‐scheme heterojunction leads to efficient photocatalytic H2 production coupled with selective 1,2‐diols oxidation. The interfacial S‐scheme charge‐transfer process was explored with transient absorption spectroscopy.